Transcriptomic Adjustments of Staphylococcus aureus COL (MRSA) Forming Biofilms Under Acidic and Alkaline Conditions - Efthimiou, Georgios; Tsiamis, George; Typas, Milton A.; Pappas, Katherine M. (Frontiers in Microbiology, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) strains are important human pathogens and a significant health hazard for hospitals and the food industry. They are resistant to β-lactam antibiotics including methicillin and extremely difficult to treat. In this study, we show that the Staphylococcus aureus COL (MRSA) strain, with a known complete genome, can easily survive and grow under acidic and alkaline conditions (pH 5 and pH9, respectively), both planktonically and as a biofilm. Α microarray-based analysis of both planktonic and biofilm cells was performed under acidic and alkaline conditions showing that several genes are up- or down-regulated under different environmental conditions and growth modes. These genes were coding for transcription regulators, ion transporters, cell wall biosynthetic enzymes, autolytic enzymes, adhesion proteins and antibiotic resistance factors, most of which are associated with biofilm formation. These results will facilitate a better understanding of the physiological adjustments occurring in biofilm-associated S. aureus COL cells growing in acidic or alkaline environments, which will enable the development of new efficient treatment or disinfection strategies.